Bibliometric analysis of immunotherapy for esophageal cancer: 2004-2024 - Hua, Yunqi; Liu, Yubo; Liu, Yanhong; Tian, Xiaoling; Zhang, Xinyi; You, Jiacong; Yin, Fangrui (Frontiers in Oncology, 2025)
Esophageal cancer (EC) remains one of the most lethal malignancies worldwide, with particularly high incidence and mortality rates in developing countries. In recent years, immunotherapy has emerged as a promising treatment strategy. This study employed bibliometric visualization tools, including CiteSpace and VOSviewer, to analyze research pertaining to immunotherapy in esophageal cancer. Based on 780 English-language publications indexed in the Web of Science database from 2004 to 2024, we quantitatively examined the research landscape, evolutionary trends, and knowledge structure of this field. The results indicated a steady increase in annual publications, with China being the leading contributor and Zhengzhou University as the most productive institution. Frontiers in Oncology and Journal of Clinical Oncology were the most prolific and most co-cited journals, respectively, while Kato Ken and Kojima Takashi were identified as the most influential scholars in the field. The research focus has shifted from traditional radiotherapy and chemotherapy to immunotherapy-related areas, such as the tumor immune microenvironment, immune checkpoint inhibitors, PD-L1 expression, and microsatellite instability. Current research emphasizes combining immunotherapy with other modalities, including radiotherapy, chemotherapy, and targeted therapy, pointing toward future multimodal combination strategies. Additionally, efforts are directed at identifying novel biomarkers to enhance treatment efficacy, reduce toxicity, and improve patient survival.